Dealing with cultural diversity in palliative care. Issue 1 (21st August 2020) - Six, Stefaan; Bilsen, Johan; Deschepper, Reginald
Abstract : Palliative care is increasingly confronted with cultural diversity. This can lead to various problems in practice. In this perspective article, the authors discuss in more detail which issues play a role in culture-sensitive palliative care, why naive culturalism will not solve such problems and in which direction research into this aspect of care can be further elaborated.